2021
DOI: 10.1272/jnms.jnms.2021_88-504
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Lentis Comfort Intraocular Lens Implantation

Abstract: To evaluate visual outcome and patient satisfaction following Lentis Comfort intraocular lens (IOL) implantation. Method: This retrospective case series examined 68 eyes of 41 patients (mean age 72.0 ± 8.1 years) who underwent Lentis Comfort (LS-313 MF15, Oculentis GmbH,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Previous studies have reported improved distance vision, higher contrast sensitivity, less halo and glare, and better image quality with Mplus series IOLs. 13 , 30 , 31 The series includes an LS-312 model with a C-loop haptics and an LS-313 model with a plate haptics, with different near addition powers from +1.5 D to +3.0 D. A previous study showed satisfactory VA of Mplus LS-312 MF30, with peaks at distance and near foci. 18 Alió et al.…”
Section: Intraocular Lens (Iol) For Presbyopia Correctionmentioning
confidence: 99%
“…Previous studies have reported improved distance vision, higher contrast sensitivity, less halo and glare, and better image quality with Mplus series IOLs. 13 , 30 , 31 The series includes an LS-312 model with a C-loop haptics and an LS-313 model with a plate haptics, with different near addition powers from +1.5 D to +3.0 D. A previous study showed satisfactory VA of Mplus LS-312 MF30, with peaks at distance and near foci. 18 Alió et al.…”
Section: Intraocular Lens (Iol) For Presbyopia Correctionmentioning
confidence: 99%
“…The lens has an optical loss of 5% and is designed to focus 95% of the time, resulting in good postoperative contrast sensitivity. [10][11][12][13] Another lens, a monofocal IOL (ZCB00 [Johnson & Johnson Surgical Vision, Inc., Santa Ana, CA, USA]), is made of hydrophobic transparent acrylic material. It is a one-piece, single-focal IOL with a 6.0 mm optical section that has a at aspheric front surface and negative spherical aberration, designed to minimize spherical aberration across the eye and improve contrast after cataract surgery.…”
Section: Introductionmentioning
confidence: 99%
“…It is a one-piece, multifocal IOL composed of hydrophilic, transparent acrylic material, with a segmental aspheric optical section in one half for distance and in the other half that provides + 1.5 D near addition. The lens has an optical loss of 5% and is designed to focus 95% of the time, resulting in good postoperative contrast sensitivity [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%